Relationships With Parents, Identity Styles, and Positive Youth Development During the Transition From Adolescence to Emerging Adulthood. Issue 1 (February 2018) - Kaniušonytė, Goda; Žukauskienė, Rita
The purpose of this study was to examine the links between relationships with parents, identity styles, and positive youth development (PYD), conceptualized as "contribution" to self, family, and community, in Lithuanian youth during the transition from adolescence to emerging adulthood. In Study I, we sought to examine how positive relationships with parents predict contribution with the potential mediating role of autonomy-supportive parenting. Participants ( N = 153) filled a self-reported questionnaire in the final year of school and 1 year later. In Study II, we aimed at investigating how parental autonomy support is related to the contribution and the potential mediating role of identity processing style. Participants ( N = 254) were assessed 1 year after graduating high school. Overall, the findings indicated that positive relationships with parents play an important role in successful adjustment and that this relationship is partially mediated by identity style. To conclude, the way in which parents respond to their children's need for autonomy and relatedness affects the adequate identity management and overall positive development during emerging adulthood.